Potential of green tea (Camellia sinensis L.) in improving liver function in mice induced by monosodium glutamate (Msg) - Derek Conrado (Global Writing Academica Researching and Publishing, 2023)
This study aims to examine the histological conditions of the liver given green tea in MSG-induced mice and to analyze the potential of green tea (Camelia sinensis L.) in improving liver function in MSG-induced mice. The research was conducted for 30 days with test animals in the form of male mice strain Balb / c. This study used a factorial completely randomized design (CRD). Each treatment consisted of P0 as a control given distilled water 0.5 ml / w / day, P1 given 0.015 g / w / day green tea, P2 which was given MSG 0.84 g / w / day, P3 which was given MSG 0, 84 g / w / hr and 0.015 g / bb / hr green tea. The results showed that the MSG induction dose of 0.084 g / w / hr had an impact on reducing liver weight, increasing ALT levels and hepatocyte diameter. The administration of green tea with a dose of 0.015 g / bb / day in mice induced by MSG and without induction of MSG was able to increase liver weight, decrease ALT levels and hepatocyte diameter. The interaction of MSG and green tea occurs in the diameter of the hepatocytes, so it can be concluded that giving green tea a dose of 0.015 g / w / hr is able to repair damage to hepatocytes caused by MSG induction of 0.084 g / w / day.